2022
DOI: 10.1111/are.15848
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of fish protein hydrolysate improves growth, feed efficiency and immune response in freshwater carnivore fish, Channa striata fingerlings

Abstract: The effect of dietary fish protein hydrolysate (FPH) at inclusion levels of 0% (control), 5% (FPH5), 10% (FPH10) and 15% (FPH15) (w/w) on growth, digestive enzyme activity, immune response and antioxidant status of striped murrel, Channa striata (4.18 ± 0.04 g), was evaluated. The dietary FPH inclusion had significantly increased weight gain (WG), specific growth rate (SGR), protein efficiency ratio (PER) and decreased feed conversion ratio (FCR) compared with the control (p < 0.05). The specific activities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 97 publications
(146 reference statements)
2
5
0
Order By: Relevance
“…The increased FCs by AIPH inclusion were due to the increased TFI translated into superior growth capabilities. Our results concurred with earlier findings of Siddaiah et al (2022).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The increased FCs by AIPH inclusion were due to the increased TFI translated into superior growth capabilities. Our results concurred with earlier findings of Siddaiah et al (2022).…”
Section: Discussionsupporting
confidence: 94%
“…The latter, activated during hydrolysis with their hydrophobic features, can enhance their interaction with lipids and support their greater antioxidant properties (Wen et al, 2020). These findings were supported by earlier researches (Fan et al, 2022; Shaghayegh et al, 2019; Siddaiah et al, 2022). Additionally, it was reported by Arise et al (2019) that AIPH generates peptide fractions with antioxidant characteristics.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…On the other hand, whole‐body lipid of Japanese flounder increased with increasing FPH inclusions from 23 to 45 g/kg and then declined with a further increase in FPH from 67 to 90 g/kg (Zheng et al, 2014). Siddaiah et al (2022) also reported increased lipid in striped murrel Chana striata fed diet containing 100 g/kg FPH, while higher dietary FPH supplementation of 150 g/kg resulted in a reduced lipid level. A similar trend was reported in turbot (Wei et al, 2016; Xu et al, 2016) and pike silverside Chirostoma estor (Ospina‐Salazar et al, 2016) as whole‐body lipid levels reduced at certain dietary FPH levels (Espe et al, 2012; Xu et al, 2016; Zheng et al, 2014).…”
Section: Discussionmentioning
confidence: 94%